Awareness of H1N1 influenza (swine flu) among rural population of Chittoor district, Andhra Pradesh - Ade, Anju Damu; Yamasani, Bhavani; Kondagunta, Nagaraj (International Journal Of Community Medicine And Public Health, 2018)
Background: Influenza is an acute respiratory tract infection caused by influenza virus, of which there are 3 types- A, B and C. All known pandemics were caused by influenza A strains. The objectives of the study were to study the awareness of H1N1 influenza (swine flu) among rural population and to examine the association between socio demographic variables and awareness of H1N1 influenza (swine flu). Methods: A cross-sectional study was carried out in the three villages of Chittoor district (Amudala Kona, Rupalanaik Thanda, Kothakadapalli) where health camps were conducted. A total of 167 rural adults were interviewed who attended the camps. Results: Majority of the study participants were illiterates (50.3%).Only 59 (35%) participants previously heard about the disease H1N1 influenza (swine flu). Majority of them 26 (44.1%) didn’t knew the cause of swine flu. Media was the most common source of information (76.3%). Only 49.2% of participants were aware about transmission of disease. Majority of them were not aware i.e. 36 (61%)regarding treatment and investigation availability for H1N1 influenza (swine flu), but only 15.3% people were aware about the vaccine availability for the disease. Conclusions: Overall awareness regarding H1N1 flu was low among rural adults. Low awareness denotes poor mass media coverage in rural community. As most of the participants are illiterates, use of TV and mass media as an effective media to dissipate information must be utilized to maximum. Awareness generated by health staff is not significant. Health workers at primary level should be equipped with knowledge and skills in order to create awareness and organize Health education sessions in all areas which can be made more effective by involving Public Health Professionals to develop communication messages.